Iodine supplementation and thyroid status in iodine deficient risk groups in rural regions of Belarus in 1999–2016 - Petrenko, Sergey V.; Dardynskaia, Irina V.; Leushev, Boris Y.; Mokhort, Tatiana V.; Kolomietz, Natalia D.; Fedorenko, Ekaterina V.; Mokhort, Elena G.; Bartoshevich, Olga A. (Journal of the Belarusian State University. Ecology, 2018)
The stable indexes of iodine supplementation and thyroid status was found in schoolchildren and pregnant women from rural iodine deficient areas of Belarus in 1999–2016. Median urinary iodine excretion level increased from 165,7 µg/l in 2015 to 233,0 µg/l in 2016 in children. In pregnant women also, there was found the increasing of median excretion of iodine from 107,5 µg/l in 2015 to 149,1 µg/l for that period of time. The figures of goiter rate in children were also increased from 7,8 to 7,3 per cent and from 16,7 to 14,7 per cent in pregnant women. The data evidence that Belorussian model of iodine deficiency elimination occurred to be effective almost in all risk groups except pregnant women from rural area.
Keywords: median of iodine excretion; goiter; children; pregnant women; rural area